Impact of Perceived Product Value on Customer-Based Brand Equity: Marx’s Theory – Value-Based Perspective - Qiao, Yonggang; Yin, Xirui; Xing, Gao (Frontiers in Psychology, 2022)
Branding has become a significant phenomenon that has been studied by the academicians and scholars. Improving the overall equity of the brand require strategies that must be implemented by the brand managers. Therefore, the investigation aimed to analyze the impact of product perceived value on customer-based brand equity with the mediating roles of brand resonance and customer affective commitment. To conduct the present study, the data was acquired from 297 customers of branded products in China. The data was then examined using structural equation modeling (SEM) technique and Smart PLS software. Product perceived value had a significant effect on customer-based brand equity. Product perceived value was also observed to have a significant effect on brand resonance and affective commitment. Furthermore, it was also concluded that both brand resonance and affective commitment played a mediating role between product perceived value and customer-based brand equity. Theoretically, the study contributed to the literature by examining the influence of product perceived value on customer-based brand equity. The study also enriched the literature by providing key findings related to the mediating roles of brand resonance and customer affective commitment. Practically, the study is beneficial for the brands and they can enhance product perceived value by improving product design, effectively communicating product benefits, and executing effective promotional strategies. Based on the limitations of the study, the study provided future directions such as increasing the sample size, including other mediating variables, and using longitudnal study design.